Introduction to the Special Issue: Bullying and Its Linkage to Other Forms of Violence - Hong, Jun Sung (Journal of interpersonal violence, 2022)
As studies have documented, children and adolescents who are identified as bullies, bully victims, or both are at an elevated risk of being involved in other forms of violence, for example, dating violence and sexual violence. Moreover, those who are exposed to violence (e.g., exposure to community violence) have increased odds of being involved in bullying. This special issue brings together scholars from a variety of disciplines (e.g., psychology, criminology/criminal justice, and social work) to investigate how involvement in bullying and other forms of violence are interrelated.